“We just want to sing”: how a small London evangelical church responded to Covid-19 - Lee, Siew-Peng (Journal of contemporary religion, 2024)
This article documents the myriad ways in which a north London evangelical church responded to Covid-19 when it was decanted from its church building into cyberspace. By focusing on three aspects of Hovland’s framework of place-making—materiality, personhood, and transcendence (Hovland 2016), I analyse how church members viewed their experience of attending an online church. Apart from contributing to the literature on non-charismatic, non-Pentecostal evangelicalism, it suggests that the importance of singing together, as well as the silence and bodily stillness that sometimes ensue, in the everyday life of a church deserves further attention in a comparative anthropology of Christianity.